Expression of defence-related genes in sunflower infected with broomrape. Issue 4 (3rd July 2016) - Şestacova, Tatiana; Giscă, Ion; Cucereavîi, Aliona; Port, Angela; Duca, Maria
ABSTRACT: Transcriptional activity of four defence-related genes ( NPR1, PAL, defensin and PR5 ) in seven sunflower lines – resistant (MS-2161A), tolerant (MS-2039A) and susceptible (MS-2098A, MS-2091A, MS-2077A, MS-2067A and MS-1589A), infected with three broomrape populations (Tulcea, Romania; Soroca and Anenii Noi, Republic of Moldova), was studied in advanced stages of infection (90 days after sowing). Obtained results revealed that resistant genotypes are characterized through higher stability in transcriptional activity of the studied genes. Thus, resistance could be associated with ability rapidly to maintain and recover a normal level of metabolism under more intensive stress factors. Also, it was established that expression of PR5 and defensin genes was altered and revealed considerable deviations in this phase of adaptation, while NPR1 and PAL mostly showed values at the level of the control group, which allows assuming that these genes, in the moment of sample collection and analysis, had normalized transcriptional activity, probably being involved in early responses.